Innovation in Authentic Assessment of Maharah Qira’ah in the Textbook of Al-’Arabiyyah Baina Yadaik Volume II - Hasna, Tsania Sausan; Baroroh, R. Umi; Firdaus, Ananda Zalfa; Adira, Wafa' Rizqiyya; Ilhusna, Rofi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Authentic assessment is an assessment that can describe the development of learning. At the same time, it can assess the process and learning outcomes of students by directly observing the student learning process. The purpose of this study was to examine the assessment of reading skills in the Al-’Arabiyyah Baina Yadaik textbook Volume II and to innovate authentic assessments that can be carried out on these skills. This research method was qualitative research. The research technique used was literature study. The source used in this study was the primary source in the form of the Al-’Arabiyyah Baina Yadaik textbook Volume II. Meanwhile, the secondary sources were journals, books and other relevant data. The data analysis techniques used were content analysis and descriptive analysis by collecting data and interpreting data. The conclusion of this study was to innovate the maharah qira’ah practice in the Al-’Arabiyyah Baina Yadaik textbook Volume II with the theory of authentic assessment by giving authentic assignments to retell the content of the reading. Retelling the content of the reading is one of the productive language skills that produces ideas and thoughts. Innovation in authentic assessment by giving authentic assignments to the Al-’Arabiyyah Baina Yadaik textbook Volume II can improve the quality of improving the maharah qira’ah in Arabic learning.